Respuesta :

Step-by-step explanation:

Q3

25 - (x-8)²/4 = [100 - (x-8)²]/4

[100 - (x²- 16x + 64)]/4

(100 - x² + 16x - 64)/4 = (-x² + 16x + 36)/4

(36 + 16x - x²)/4 = (36 - 2x + 18x - x²)/4

[2(18 - x) + x(18 - x)]/4 = [(2 + x)(18 - x)]/4

....proved

Q4

3(ax + 7) - 2(x + b) = 4x + 29

expanding,

3ax + 21 - 2x - 2b = 4x + 29

3ax - 2x + 21 - 2b = 4x + 29

Comparing terms; x terms,

3ax - 2x = 4x

3a - 2 = 4

3a = 6

a = 6/3

a = 2

constant terms,

21 - 2b = 29

21 - 29 = 2b

2b = -8

b = -8/2

b = -4

.... proved